Metodologias para a monitorização de ruído. Combinação de medições e modelação de ruído na melhoria da eficiência na amostragem de ruído - Antunes, S. (2012)
The Environmental Acoustics Portuguese legislation established the day-evening-night (Lden) and night (Ln) noise indicators, determined during the year, as the noise descriptors to be used for verification of compliance with limit values. When making noise measurements several sampling strategies can be used, as well as strategies that combined both the stratification of the measurement points and the use of noise models calculation. This article presents a summary of the main strategies that can be used, as well as two case studies.